Green Building Practices on Waste Minimization in China Construction Industry - Lee, Bernice Xin Yi; Ponraj, Mohanadoss; Widyasamratri, Hasti; Wang, Jie (Tecno Scientifica Publishing, 2021)
In China, a common practice for construction waste management is to dispose of it in landfills. A 5% construction waste recycling rate and ongoing insufficient landfilling practice resulted in decreased environmental and socioeconomic well-being. Management hierarchy that starts with rethink, redesign, reduce, reuse, refurbish, recycle, incineration, and finally disposal is a probable strategy to facilitate construction waste minimization in China. The green building concept pursued by China also served as a promising tool in evaluating the performance of Chinese green buildings. Barriers include lack of standard operating procedure in waste minimization, immature recycling technology and an undeveloped recycling market, leading to poor performance in construction waste minimization. Several strategies are proposed to ameliorate the current condition in China's construction sector. Even though results reveal that China falls behind in the engagement of green building compared to developed countries, green materials are utilized in various building structures such as flooring, roofs, walls, and outdoor pavements. Lastly, the benefits and shortcomings of two green material technologies, in particular material selection and recycling, applied in China were reviewed.